1993
DOI: 10.1016/0735-1097(93)90045-3
|View full text |Cite
|
Sign up to set email alerts
|

Vasotonic angina: A spectrum of ischemic sysdroms involving function abnormalities of the epicardial and microvascular coronary circulation

Abstract: These findings indicate that vasoconstrictor stimuli may trigger a diffuse abnormal response of both epicardial and resistance vessels in some patients with chest pain and angiographically normal coronary arteries. Patients showing such diffuse vasoconstrictor abnormalities are suggested to have a single pathogenetic entity with a spectrum of ECG manifestations ranging from ST depression to ST elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 27 publications
1
31
0
4
Order By: Relevance
“…Thus, in CSX patients functional abnormalities in the epicardial coronary vessels were reported in previous studies showing impaired endothelium-dependent vasodilatory function in response to vasodilator stimuli and increased vasoconstriction in response to a ergonovine test. 8,9 Similarly, in VA patients, functional alterations of coronary microcirculation were reported in some studies. 10,11 However, no previous studies described clinical symptoms compatible with both forms of angina, suggesting a clinically relevant impairment both of epicardial and microvascular function in the same patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, in CSX patients functional abnormalities in the epicardial coronary vessels were reported in previous studies showing impaired endothelium-dependent vasodilatory function in response to vasodilator stimuli and increased vasoconstriction in response to a ergonovine test. 8,9 Similarly, in VA patients, functional alterations of coronary microcirculation were reported in some studies. 10,11 However, no previous studies described clinical symptoms compatible with both forms of angina, suggesting a clinically relevant impairment both of epicardial and microvascular function in the same patients.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies, however, suggested that functional abnormalities in large coronary arteries may be present in CSX patients. 8,9 Similarly, abnormalities in coronary microcirculation have been described in VA patients. 10,11 No previous study, however, reported clinical evidence of the simultaneous occurrence of angina episodes typical of both VA and of CSX in the same patients.…”
Section: Introductionmentioning
confidence: 89%
“…раздел 6.7.1. по микрососудистой стенокардии) [498]. Тем не менее, замечание о том, что у этих женщин име-ются "нормальные" коронарные артерии, должно быть пересмотрено в свете дополнительного исследо-вания с ВСУЗИ у женщин в рамках исследования WISE (Women's Ischemia Syndrome Evaluation), кото-рое показало, что в выборке из 100 таких женщин приблизительно у 80% имелся определенный коро-нарный атеросклероз, который сопровождался поло-жительным ремоделированием артерий [499].…”
Section: повторная реваскуляризация у пациентов с предыдущим коронарнunclassified
“…1,2 Endothelial dysfunction may reside at both epicardial and microvascular levels that may be consistent with both the abovementioned hypotheses. 22 Endothelial dysfunction could be, therefore, a common pathway of different causes leading to chest pain of patients with normal angiograms. It may be due to increased superoxide anion-mediated inactivation of nitric oxide, which causes oxidative stress.…”
Section: Endothelial Dysfunction In Angina With Normal Angiogramsmentioning
confidence: 99%